2016
DOI: 10.1021/acs.joc.5b02602
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Isocoumarins via Silver(I)-Mediated Annulation of Enol Esters

Abstract: Silver-mediated annulation of 2-iodo enol esters leading to 4- and 3,4-substituted isocoumarins was accomplished selectively at room temperature. Coupling of 2-iodo benzoic acids with enolates that were produced in situ from the simple esters was also performed to produce isocoumarins under analogous reaction conditions. Owing to the mildness of the current protocol, 4-acyl 3-substituted isocoumarins were efficiently produced without any deacylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…A silver acetate‐mediated annulation reaction of 2‐iodoenol esters was reported for the synthesis of substituted isocoumarins (Scheme ) …”
Section: Recent Advances In Isocoumarin Synthesismentioning
confidence: 99%
“…A silver acetate‐mediated annulation reaction of 2‐iodoenol esters was reported for the synthesis of substituted isocoumarins (Scheme ) …”
Section: Recent Advances In Isocoumarin Synthesismentioning
confidence: 99%
“…[23] Finally, Panda et al described the silver-mediated cyclization of 2-iodo enol esters to afford 7-halo 3,4-disubstituted isocoumarins in moderate to good yields. [24] As a result of our previously established methodology [17,18] and to prepare a unified way to extend the functionalities of this interesting heterocycle, we report in this paper a very mild and convenient copper-catalyzed route to synthesize exclusively 5,7-diiodo-3-substituted isocoumarins by starting from 2,3,5-triiodobenzoic acid (Scheme 2).…”
Section: Introductionmentioning
confidence: 95%
“…More recently, Shang et al reported the rhodium(III)‐catalyzed C–H activation/esterification reaction for the synthesis of isocoumarins that contain a bromine or chlorine atom on the aromatic ring . Finally, Panda et al described the silver‐mediated cyclization of 2‐iodo enol esters to afford 7‐halo 3,4‐disubstituted isocoumarins in moderate to good yields …”
Section: Introductionmentioning
confidence: 99%
“…Enol esters represent an important class of synthons in organic chemistry, commonly employed as intermediates, among others, in cross-coupling [1][2][3], asymmetric hydrogenation [4][5][6], and cyclization reactions [7][8][9], as well as monomers in polymerization and oligomerization processes [10][11][12]. Among the different methods of synthesis of these valuable molecules, the intermolecular addition of carboxylic acids to alkynes catalyzed by transition metals (hydro-oxycarbonylation reaction) is probably the most straightforward and atom-economical one because the starting materials are widely available and no byproducts are generated in the process.…”
Section: Introductionmentioning
confidence: 99%